CLIMATE RISK MANAGEMENT AND SUSTAINABLE FINANCE: CHALLENGES IN INDONESIA’S GREEN BANKING SECTOR - Indira Shofia Maulida; Ruswaji Ruswaji; Indah Kurniyawati; Lilik Nurcholidah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Climate change poses significant risks to the banking sector, particularly in terms of asset stability and sustainable financing. Indonesia, as a developing country, faces unique challenges in implementing climate risk management and sustainable finance practices. This study employs a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize research on climate risk management and sustainable finance within Indonesia’s green banking sector. Data were collected from Scopus, Web of Science, ScienceDirect, Google Scholar, as well as official reports from OJK, World Bank, and NGFS, with inclusion criteria for articles published between 2017 and 2024. The review of 25 articles indicates that the main challenges include limited climate risk data, suboptimal integration of climate risks into bank risk management, low profitability of green financing, and inconsistent disclosure standards. The study concludes that enhancing technical capacity, regulatory harmonization, and transparency in reporting are essential to accelerate green banking implementation in Indonesia. This research also provides a basis for developing a more contextualized climate risk framework for national banks.